Best Practices of a High-Achieving Teacher Education Institute in Asia - Saban, Gracel Ann S. (11th International Scholars Conference, 2018)
“Best Practices” are anchored on solid learning principles. Scholars and accrediting agencies have put these “practices” at the core of various professional programs (MacCallum & Ross, 2010). This qualitative study aimed to identify the best practices of a high-achieving teacher education institute in Asia. This premiere institution is considered high-achieving due to its standing in the World University Rankings in recent years. Piaget’s theory of Constructivist learning has had wide ranging impact on learning theories and teaching methods in education and is an underlying theme of many education reform movements. An appreciative inquiry research design was employed to draw out the best practices of the high-achieving teacher education institute. Data were gathered through one-on-one in-depth interviews with 10 participants: five faculties, three students, and two alumni. Interview data were transcribed and analyzed using Seidel’s Qualitative Data Analysis Model of noticing, sorting, and classifying. Findings show that the best practices include empowerment of the teaching profession, implementation of a balanced program, contextualization and diversity of practice, application of a highly constructivist pedagogy, and openness to multiple perspectives. These findings imply the importance of quality teacher preparation through instructional quality, service learning, and overseas exposure. It is therefore recommended that Teacher Education Institutions consider holistic training of pre-service teachers that includes not only equipping the academic realm but also the spirit and service facets.